Analisis peforma turbin ulir (archimedes screw) dengan variasi tekanan - aldio syafiq abidin (Jurusan Teknik Mesin, 2022)
This screw type water turbine was once a device used to pump water. This screw type water turbine operates with low rotation and is still relatively new to be developed and has great potential for rivers or irrigation canals that have low slopes. This turbine has several advantages over other types of low head turbines, namely that it does not have a special control system. In the picture it can be seen the mechanism by which water from the lower reservoir is flowed to the upper reservoir by using a pump, the purpose of the upper reservoir is to stabilize the discharge of water that comes out. When the water has come out it will be passed through the screw, later this water will rotate the screw. This rotation will be transmitted to the generator and generate electricity. The water that has come out will go down to the bottom reservoir and be continued by the pump and will repeat itself. The generator already has a cable that will be used to take data using a multimeter and ampere pliers. Don't forget to also take rotation data using a tachometer. After the desired data has been obtained, you can move on to the next pressure. As for the maximum angle, the pressure is 25 Psi because the water is more optimal when it passes through the screw so that the resulting rotation is greater.